Integracja regionalna UE a reguły GATT/WTO - Skrzypczyńska, Joanna (Rocznik Integracji Europejskiej, 2015)
The main purpose of regional integration is to remove trade barriers between participant countries and set up trade barriers against third countries. The European Union, on the one hand, established a single market, thereby creating a free trade area between member countries, on the other hand, it uses a variety of protection mechanisms towards third countries. The aim of the paper is to analyse trade rules under the GATT and the European integration process. The paper also examines how European integration deals with the rules of regional agreements established under Article XXIV of the GATT.